Role of human-computer interaction factors as moderators of occupational stress and work exhaustion - Anantharaman, Reddiyoor Narayanaswamy (Taylor & Francis Group, 2005)
Software professionals perform boundary-spanning activities, and thus need strong interpersonal, technical, and organizational knowledge to be professionally competent. They have to perform in a demanding work environment characterized by strict deadlines, differing time zones, interdependency in teams, increased interaction with clients, and extended work hours. These characteristics lead to occupational stress and work exhaustion. Yet, the impact of stress is felt in different ways by different people, even if they perform the same functions. These differences in the perception of stress can be caused by varying confidence in their technical capabilities. People possess varying technical capabilities, based on their acquisition of technical skills, comfort level in using the technology, and intrinsic motivation. These attributes represent the human-computer interaction (HCI) personality of software professionals. This article examines whether these HCI factors moderate the relationship between occupational stress and work exhaustion. Data were collected from software professionals located in Chennai and Bangalore in India. The data revealed that HCI factors had a main effect but no significant moderating effects on work exhaustion. The control over the technology variable emerged as the key variable among the HCI factors that affected software professionals' ability to cope with stress and work exhaustion.